The Revised Method for Calculating of The Optimal Train Control Mode - ZHELIEZNOV, Konstantyn; AKULOV, Artem S.; ZABOLOTNYI, Oleksandr M.; URSULYAK, Lyudmila V.; CHABANUK, Evgenij V.; SHVETS, Angela O.; KUZNETSOV, Valeriy G.; RADKEVYCH, Anatolii V. (Archives of Transport, 2019)
Development of a method for calculating the optimal mode of conducting a train in terms of energy saving meet the safety requirements and schedules. The method of calculation must solve the assigned tasks without significant time spent on the calculation. To implement this method of calculation was used a simplified model of the train as a controlled system. The existing mathematical and algorithmic methods for solving isoperimetric problems of finding the optimal solution in the presence of restrictions on resources were the information base for methodology development. Scientific works of domestic and foreign scientists, professional periodicals, materials of scientific and practical conferences, methodical and normative materials, currently in force on Ukrainian Railways. The results of these studies were used to create simulators on the basis of computer technology for the training of locomotive drivers. The scientific novelty of the proposed calculation method consists in applying the simplified calculations of the status of the train as a controlled system, without the use of differential equations of motion that allows to significantly increase the speed of the calculations. This, in turn, will solve the problems of finding optimal control in real time, taking into account changing conditions during the movement of the train. The practical significance of the obtained results is the use of such a calculation method that does not require significant time for its implementation and can be used as a subsystem of the on-board train control system capable of performing calculations taking into account changes in the current train situation.